2013
DOI: 10.1016/j.molimm.2013.05.228
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmune semaphorin 4D is necessary for optimal lung allergic inflammation

Abstract: Neuroimmune semaphorin 4D (Sema4D) was found to be expressed and function in the nervous and immune systems. In the immune system, Sema4D is constitutively expressed on T cells and regulates T cell priming. In addition, it displays a stimulatory function on macrophages, DC, NK cells, and neutrophils. As all these cells are deeply involved in asthma pathology, we hypothesized that Sema4D plays a critical non-redundant regulatory role in allergic airway response. To test our hypothesis, we exposed Sema4D−/− and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 52 publications
3
23
0
Order By: Relevance
“…In contrast, Sema4D 2/2 mice demonstrated reduced allergic lung inflammatory cell infiltration, lung Th2 and proinflammatory cytokine contents, and humoral anti-allergen responses (20). The exacerbated inflammatory lung response in Sema4A 2/2 mice was accompanied by the significantly lower numbers of Treg cells in spleens and lungs, whereas this was the opposite for Sema4D 2/2 mice (19,20). Treatment of Sema4A 2/2 mice with recombinant Sema4A (rSema4A) resulted in not only significantly reduced allergic airway responses but also increased numbers of lung Treg cells (21).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast, Sema4D 2/2 mice demonstrated reduced allergic lung inflammatory cell infiltration, lung Th2 and proinflammatory cytokine contents, and humoral anti-allergen responses (20). The exacerbated inflammatory lung response in Sema4A 2/2 mice was accompanied by the significantly lower numbers of Treg cells in spleens and lungs, whereas this was the opposite for Sema4D 2/2 mice (19,20). Treatment of Sema4A 2/2 mice with recombinant Sema4A (rSema4A) resulted in not only significantly reduced allergic airway responses but also increased numbers of lung Treg cells (21).…”
Section: Introductionmentioning
confidence: 84%
“…We previously investigated the roles of two neuroimmune Sema, Sema4A and Sema4D, in allergic asthma in vivo. We demonstrated that these two distinct members of the class IV Sema family of proteins display opposite effects on asthma severity (19,20). Sema4A 2/2 mice exhibited an exacerbated response to allergen challenge that included increases in eosinophilic airway infiltration, lung local Th2 cytokine secretion, bronchial epithelial cell hyperplasia, airway hyperresponsiveness to methacholine challenges, and allergen-specific Ab content in serum (19).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Nkyimbeng-Takwi et al (42) found that Sema4a 2/2 mice had higher baseline AHR and were hyperresponsive to OVA challenge. Sema4d 2/2 mice had low airway eosinophilia, normal basal AHR, and modest decreases in airway inflammation (43).…”
Section: Discussionmentioning
confidence: 91%
“…It affected T cell activation and function suggesting its positive costimulatory role. 12 Further studies are required to define the function of eosinophil-expressed sema4D in lung allergic inflammation. Letter to the Editor / Allergology International xxx (2015) 1e3…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%